The rest-less ghost, or, Wonderful news from Northamptonshire and Southwark : being a most true and perfect account of a persons appearance that was murdered above two hundred and fifty years ago : first about three weeks since, to one William Clarke at Hennington in Northampton-shire, whom it appointed to meet in Southwark, and did there appear to him again, and several others, on Sunday last, the 10th of this instant January : where it discovered a great parcel of money, and some writings buried in the ground, which were disposed off by his order, and then seeming satisfied it disappeared : this relation is taken from the said Will. Clarks own mouth, who came to London on purpose, and will be attested and justified by Will. Stubbins, Iohn Charlton, and John Steven, to be spoken with any day, at the Castle Inn without Smith Field-Barrs, and many others. (1675)
Summary goes here